2019
DOI: 10.3390/vaccines8010005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Communicative and Informative Strategies on Influenza Vaccination Adherence and Absenteeism from Work of Health Care Professionals Working at the University Hospital of Palermo, Italy: A Quasi-Experimental Field Trial on Twelve Influenza Seasons

Abstract: Every year, about 20% of health care workers (HCWs) acquire influenza, continuing to work and encouraging virus spreading. Influenza vaccination coverage rates and absenteeism from work among HCWs of the University Hospital (UH) of Palermo were analyzed before and after the implementation of several initiatives in order to increase HCWs’ awareness about influenza vaccination. Vaccines administration within hospital units, dedicated web pages on social media and on the UH of Palermo institutional web site, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…However, the vaccination coverage registered in our teaching hospital represents an encouraging starting point and it is analogous, or even higher, than flu vaccination coverage rates registered in other national and regional settings [29,32,33,39,50,[53][54][55]. Our results confirmed that physicians are the professionals most willing to get vaccinated, as reported in the literature [20,33,50,54], even though the overall increase was the lowest during the considered period if compared to nurses and OHCWs. The job category that registered the highest increase in coverage rate (compared to the previous years) were the OHCWs (+76.3%) and the nurses (+75.8%), proving that the implemented strategies were effective in reaching groups originally less inclined to vaccination, maybe due to the wrong perception of being at low risk of illness or transmitting the infection.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the vaccination coverage registered in our teaching hospital represents an encouraging starting point and it is analogous, or even higher, than flu vaccination coverage rates registered in other national and regional settings [29,32,33,39,50,[53][54][55]. Our results confirmed that physicians are the professionals most willing to get vaccinated, as reported in the literature [20,33,50,54], even though the overall increase was the lowest during the considered period if compared to nurses and OHCWs. The job category that registered the highest increase in coverage rate (compared to the previous years) were the OHCWs (+76.3%) and the nurses (+75.8%), proving that the implemented strategies were effective in reaching groups originally less inclined to vaccination, maybe due to the wrong perception of being at low risk of illness or transmitting the infection.…”
Section: Discussionsupporting
confidence: 86%
“…Vaccination among HCWs involved in the everyday care of patients limits the spread of the virus, ensuring healthcare assistance continuity, thanks to both the individual and herd immunity [13,14,17,18]. Moreover, it reduces absenteeism [8,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…During the observation period, absenteeism work in vaccinated HCWs resulted to be far lower than among non-vaccinated colleagues, either considering the whole observation period or focusing on the 2017–18 influenza epidemic peak [ 36 ], thus confirming the existing relation between HCWs influenza vaccination coverage and absenteeism [ 19 , 21 23 , 37 39 ]. Even if some colleagues suggest the existence of a ceiling effect when vaccine coverage is over 40% [ 40 ], Italian and European results are still under this risk rate and therefore more efforts are needed to improve adherence.…”
Section: Discussionmentioning
confidence: 71%
“…On one hand, Wilde et al found that influenza vaccination did not reduce absenteeism among HCWs [19] and the study of Gianino et al seems to confirm this evidence in the Italian context as well [20]. On the other hand, non-specific [21] and ILI-related [22] absenteeism among HCWs were significantly reduced by influenza vaccination; this evidence was confirmed by the recent Costantino et al work which found a correlation between the increase in influenza vaccination coverage and the reduction of lost days of work [23].…”
Section: Introductionmentioning
confidence: 79%
“…At the University Hospital (UH) of Palermo, Italy, a quasi-experimental field trial was conducted from 2007 to 2019 in order to evaluate vaccination increase during consecutive influenza seasons among health care workers (HCWs) of the UH of Palermo after communicative and informative tailored strategies were adopted, and the impact of this increase on the reduction of working days lost due to acute sickness during influenza season [ 11 ].…”
Section: Manuscripts Included In the Special Issuementioning
confidence: 99%